Participation and ownership in PRS : not enough civil society, too much World Bank - Eberlei, Walter (2003)
Analyzes the procedural dimensions of the Poverty Reduction Strategies (PRS) approach. Discovers a positive picture overall, but still finds serious shortcomings in terms of ownership and participation.